Razmerje med misicno mocjo antropometricnimi lastnostmi in gibalnimi sposobnosti otrok, starih 11-12 let - Pejcic, A.; Zvan, M.; Krstulovic, S. (Kinesiologia Slovenica, 2004)
To gain deeper insight into the integral anthropological status of children 11-12 years of age, the 11-test and measure battery, assessing anthropological status, was applied on a sample of 1058 primary school fourth-graders (540 boys and 518 girls). In the study three variables measuring muscular strength were criterion variables, whereas four anthropometric and four motor variables were the predictor variables. Canonical correlation analysis revealed that in the subsample of boys the two pairs of canonical factors were determined. Boys performed better in the tests of explosive leg power and isometric arm strength endurance if they had lower values of body mass, subcutaneous fat, and body voluminosity, and better gross body co-ordination and aerobic endurance. According to the second canonical factor boys performed better in the trunk strength endurance of a dynamic type test if they had better scores in the movement frequency and hamstrings flexibility tests. In the subsample of girls the statistically significant association existed only in the first pair of canonical factors. Girls performed well in the strength/power tests if they had lower values of body mass and subcutaneous fat and better scores in the movement frequency, gross body coordination, flexibility and aerobic endurance tests.